Determinants of micro and small enterprises financial performance in the non-farm sector of Ghana: A quantile regression approach - Sylvester N. Ayambila (Cogent Economics & Finance, 2023)
This study estimates the factors influencing micro and small enterprise financial performance in the non-farm sector of Ghana. Data was sourced from Ghana ECG/ISSER Socio-Economic Panel Survey in 2010. The study is underpinned by the resource-based view theory of firm performance. Ordinary least squares were used to determine the factors affecting financial performance and quantile regression used to analyse the variation of financial performance among enterprises. Many variables including; gender of the enterprise owner, enterprise owner's age, technical education, enterprise years of operation, enterprise location, enterprise sub-sector, number of casual, hired labour, and enterprise value of assets significantly influenced enterprise financial performance. Enterprise resources dominated industry and sector characteristics in shaping enterprise financial performance. Inter-quantile regression results indicate that gender variable was statistically significant across six inter-quantiles emphasizing the importance of gender. Enterprises in the services sub-sector were less profitable relative to those from the manufacturing, trade and restaurant sub-sectors. The results from the quantile regressions dismiss the argument that a joint set of factors influence the financial performance of enterprises, and that those factors do not vary irrespective of whether the enterprise is performing well or not. Technical education should be promoted in order to improve enterprise performance.
Keywords: 330; Financial performance; Ghana; non-farm enterprises; ordinary least squares; quantile regression; resource-based view